An Investigation of the Symmetric and Asymmetric Cleavage Products in the System Aluminum Trihalide/1‐Butylimidazole. Issue 46 (31st July 2017) - Hog, Michael; Schneider, Marius; Studer, Gauthier; Bäuerle, Monika; Föhrenbacher, Steffen A.; Scherer, Harald; Krossing, Ingo
Abstract: Mixtures of AlX3 (X=Cl, Br) with 1‐butylimidazole (BuIm) in various ratios were investigated. The mixtures were characterized by multinuclear ( 1 H, 27 Al, 13 C, and 15 N) NMR, IR, and Raman spectroscopy and in part by single‐crystal X‐ray diffraction. Depending on the molar fraction x (AlBr3 ) of the AlBr3 ‐based mixtures, the cationic aluminum complexes [Al(BuIm)6 ] 3+ and [AlBr2 (BuIm)4 ] +, the neutral adduct [AlBr3 (BuIm)], as well as the anions Br −, [AlBr4 ] −, and [Al2 Br7 ] − could be identified as the products of the symmetric and asymmetric cleavage of dimeric Al2 Br6 . Furthermore, there are hints at the formation of [AlBr2 (BuIm)2 ] + or related cations. Comparison of the AlBr3 /BuIm system with AlCl3 ‐based mixtures revealed the influence of the halide: In contrast to AlBr3, the trication [Al(BuIm)6 ] 3+ could not be detected as main product in a 1:6 mixture of AlCl3 and BuIm. Additionally, [AlCl3 (BuIm)] crystallizes from a mixture with x (AlCl3 )=0.60 at room temperature, whereas the corresponding AlBr3 ‐based mixture remains liquid even at +6 °C. Three AlBr3 ‐based mixtures are liquid at room temperature, whereas all other mixtures are solids with melting points between 46 and 184 °C. The three liquid mixtures exhibit medium to high viscosities (117 to >1440 mPa s), low conductivities (0.03–0.20 mS cm −1 ), but high densities (1.80–2.21 g cm −3 ). Aluminum could be successfully deposited from one of the neat Lewis acidic mixtures of the AlBr3 ‐based system. Abstract : Symmetric or asymmetric? The cleavage of dimeric Al2 X6 (X=Cl, Br) by 1‐butylimidazole (see figure) was investigated by multinuclear NMR, IR, and Raman spectroscopy and in part by single‐crystal X‐ray diffraction. The formation of neutral and ionic cleavage products depends on the molar fraction x (AlX3 ). The influence of the halide on the present constituents was investigated by comparison of AlBr3 ‐ and AlCl3 ‐based mixtures. The room‐temperature liquids with x (AlBr3 )≈0.6 are suited to electrochemical Al deposition.